Suicide Ideation among Adolescent American Indians: An Application of General Strain Theory. Issue 6 (3rd June 2018) - Ivanich, Jerreed; Teasdale, Brent
ABSTRACT: The objective of this study is to compare suicidal thoughts among American Indian/Alaskan Natives (AI/AN) to a series of non-AI/AN comparison groups, using data from the National Longitudinal Study of Adolescent to Adult Health. This study uses general strain theory as the guiding framework for understanding differences between racial groups in their suicidal ideation. A statistically significant difference is present between AI/AN and comparisons in suicidal ideation. The factors that may explain these differences addressed in this study include: alcohol abuse, exposure to suicidal behavior of friends and family, depression, and gun access. Implications for prevention and treatment are discussed.